(untitled) (Research, Society and Development, 2020)
Considering the importance of knowledge about child and adolescent health in the training and performance of Physical Education teachers, the study aimed to map the theme of Child and Adolescent Health in the Pedagogical Project of the Course - PPC of a Degree Course in Physical Education at a public university. It is a descriptive, exploratory and qualitative study. The first step consisted of reading and analyzing the National Curriculum Guidelines with the intention of mapping the orientations on the referred theme. The second step was the search of themes in the disciplines that dealt with the health of children and adolescents in the PPC of the Physical Education degree course of the State University of Ceará. The results showed nine syllabuses, which directly or indirectly, were related to the theme of Child and Adolescent Health. It is noteworthy that the PPC leaves gaps in the curriculum for the possibility of complementing the qualification of teachers in specific training courses, besides that it requires from the faculty minimal knowledge on the subject to implement transversally in the different disciplines that compose the course.